1993
DOI: 10.5006/1.3316053
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Decomposition of Fe(OH)2in the Presence of AVT Chemicals and Metallic Surfaces—Relevance to Low-Temperature Feedwater Line Corrosion

Abstract: Alkalizing agents cyclohexylamine, morpholine, and hydrazine accelerate the base-induced decomposition of Fe(OH) 2 even at high pH levels by lowering the activation energy of the reaction. Efficient evolution of hydrogen is observed from Fe(OH) 2 suspension in the presence of hydrazine, while weakly stimulated evolution is observed in the presence of cyclohexylamine and morpholine. It appears that the concentration and complexing abilities of the additives critically determine the yield of hydrogen. Nickelcont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The resulting internal pressure buildup at these locations is believed to be the principal cause for embrittlement and blistering of iron and steel exposed to anaerobic environments. The rate of uptake at the surface is reaction-controlled but is proportional to the square root of the hydrogen partial pressure (Sievert's law): R = kPH°•5 (11) indicating that H2 molecules disproportionate at the iron surface and enter the iron as individual atoms rather than as diatomic molecules (26).…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting internal pressure buildup at these locations is believed to be the principal cause for embrittlement and blistering of iron and steel exposed to anaerobic environments. The rate of uptake at the surface is reaction-controlled but is proportional to the square root of the hydrogen partial pressure (Sievert's law): R = kPH°•5 (11) indicating that H2 molecules disproportionate at the iron surface and enter the iron as individual atoms rather than as diatomic molecules (26).…”
Section: 5mentioning
confidence: 99%
“…At lower temperatures, it proceeds slowly because of kinetic restraints, and Fe(OH)2 may be a metastable phase in lowtemperature anaerobic groundwater environments. However, there are known inorganic and organic compounds that can catalyze this mineralogic transformation (10,11). None of these identified catalysts, however, are major constituents of groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…The Schikorr reaction usually occurs in the process of anaerobic corrosion of iron and carbon steel in various conditions [21,22]. Herein, this reaction was used to prepare magnetite nanoplates.…”
Section: Introductionmentioning
confidence: 99%
“…The denoted hydroxide has been identified in both sediments obtained from gas and crude oil pipelines in whichever of its forms: α-FeO(OH), β-FeO(OH) or γ-FeO(OH). It has been suggested that the hydroxide is transformed, at the same time, into magnetite 39 : …”
Section: Discussionmentioning
confidence: 99%